Electromagnetic Signaling Outperforms Quorum Sensing in Bacterial Biofilms: A Communication Channel Capacity Perspective - Navid Barani; Kamal Sarabandi (IEEE Access)
There is a growing body of theoretical and experimental evidence that in addition to the biochemical signaling using auto-inducers and ion channels, biological cells and more specifically certain bacterial biofilms can transmit and receive electromagnetic (EM) waves as a means of communication. It was recently hypothesized that certain cellular structures and biofilms may be equipped with simple radios whose operation is based on mechanical antennas. For instance, biofilms produced by bacterial cells are composed of elastic helical fibers known as amyloid fibrils, which possess permanent electric dipoles. Through theoretical analysis, it was recently proposed that cells in such biofilms are capable of transmitting EM signal to their surrounding environment through mechanical vibration of these charged fibrils. This theory has been also validated experimentally by carrying careful measurements of radio emission from staphylococcus aureus biofilms. In this paper, we explore the potential biological advantages of electromagnetic (EM) signaling over chemical signaling in terms of data rate and communication range, to illustrate why such an EM signaling mechanism might evolve in certain biological cells. Basically by using communication channel modeling, channel capacities for the biochemical communication method known as quorum sensing (QS) and that for EM-based communication are evaluated and shown that EM-based communication provides much higher data rate and over longer intercellular distances.